Archaeological evidence of luxury textiles from Late Antique Serdica - Iliana Borisova-Katsarova (Българско е-Списание за Археология, 2025)
Evidence of archaeological textiles from antiquity, and in particular of luxury textiles, has long attracted the interest of researchers. Clothing in every historical period is among the clearest markers of prestige and social status. Unfortunately, we have very little published material from modern day Bulgaria. This paper presents some finds from the Eastern and Western necropolises of Serdica, which shed some light on the spread and use of gold-woven textiles in late antiquity. There are 17 examples of gold-woven clothing and funerary textiles. Most of them have only the golden threads preserved, but in some cases organic threads are also detected, which are subject to forthcoming interdisciplinary analysis. In addition to the archaeological finds, some pictural evidence are presented to complement the visual reconstruction of the luxury textiles in late antiquity.